P051: Does knowledge of the Canadian CT Head Rules impact the frequency of CT's ordered?. (15th May 2017) - Duyvewaardt, H.C.; Ertel, M.; Angel-Mira, J.; Parker,; Kandola, N.; Cheyne, M.; Brar, R.; Sidhu, H.
Abstract : Introduction: The Canadian Computed Tomography Head Rules (CCTHR) is a validated and well-known head injury clinical decision rule that allows Emergency Room Physicians (ERPs) to determine which patients are most likely to benefit from a diagnostic CT. However, this clinical decision rule is not uniformly adhered to and a number of preventable CT scans are ordered. Choosing Wisely Canada has ranked decreasing unnecessary head CT scans as the number one priority for Emergency Departments (ED). As such, the purpose of this study was to investigate if an educational intervention for ERPs would increase adherence to the CCTHR.Methods: In September 2015 the CCTHR were presented and discussed at three ED departmental meetings at Kelowna General Hospital (KGH) a large tertiary hospital in the interior of British Columbia, Canada. Educational materials were distributed to the ERPS and a CTTHR checklist was made available throughout the ED. Rates of adherence to the CCTHR criteria were calculated from MHI patients that were seen in the four years prior to the educational intervention and were compared to rates of adherence for patients 12 months post educational intervention. Only patients that agreed to participate in the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) were included in this analysis. Differences in adherence rates were tested using the chi-squared test.Results: 477 patients were included in the analysis for the pre-education cohort (control) and 257 for the post-education cohort(intervention). In the control cohort, 348 of the 477 (73%) of the patients were managed in accordance to the CCTHR compared to 194 of the 257 (75%) in the intervention cohort. There was no statistically significant difference in rates of adherence ( p =0.457).In the control cohort, 44 of the 321 (14%) of patients received a CT that did not meet any CCTHR criteria compared to 15 of the 163 (9%) in the intervention cohort. The overall CT imaging rate was 24% in each patient cohort.Conclusion: Although adherence rates between the two cohorts were not statistically different, a greater proportion of patients had a CTAS of 2 or 3 and met criteria in the intervention cohort suggesting a higher level of acuity. Imaging rates remained constant at 24%, which was lower than expected if there was full adherence to the CCTHR. Further study is required to determine if educational interventions can improve adherence to the CCTHR.